2009
DOI: 10.1128/jcm.00460-09
|View full text |Cite
|
Sign up to set email alerts
|

Trichosporon mycotoxinivorans , a Novel Respiratory Pathogen in Patients with Cystic Fibrosis

Abstract: This report describes the molecular epidemiology, in vitro susceptibility, colonial and microscopic morphologies, and biochemical features of Trichosporon mycotoxinivorans, a newly recognized pathogen that appears to have a propensity for patients with cystic fibrosis. The index patient died with histologically documented Trichosporon pneumonia complicating cystic fibrosis. This is also the first report of disease caused by a Trichosporon species in a nontransplant patient with cystic fibrosis. As T. mycotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 29 publications
2
56
1
Order By: Relevance
“…It appeared to be phylogenetically closely related to Trichosporon loubieri, a nonpathogenic species. T. mycotoxinivorans was initially considered nonpathogenic, until the first case of invasive and fatal pneumonia in a nontransplanted CF patient was reported in 2009, followed by the retrospective identification of three additional cases in CF patients from archived clinical samples, suggesting a propensity of T. mycotoxinivorans for colonizing airways in CF patients (9).…”
Section: Case Reportmentioning
confidence: 99%
“…It appeared to be phylogenetically closely related to Trichosporon loubieri, a nonpathogenic species. T. mycotoxinivorans was initially considered nonpathogenic, until the first case of invasive and fatal pneumonia in a nontransplanted CF patient was reported in 2009, followed by the retrospective identification of three additional cases in CF patients from archived clinical samples, suggesting a propensity of T. mycotoxinivorans for colonizing airways in CF patients (9).…”
Section: Case Reportmentioning
confidence: 99%
“…The proximity of the yeast strains isolated in this study to T. mycotoxinivorans varied between 99% (CBA-506, CBA-531) and 100% (CBA-507) identity. These Trichosporon species have been previously described as pathogenic yeasts (Girmenia et al, 2005;Hickey et al, 2009;Sharman et al, 2010;Gabriel et al, 2011). These species share a close similarity in the phylogenetic tree based on the D1/D2 regions of the 26S ribosomal DNA, and the (approximately) 600-bp 18S ribosomal DNA.…”
Section: Discussionmentioning
confidence: 88%
“…It occurrence was also described in grape marc in southern Peloponnese, Greece, by Ntougias et al (2010), which reports it as closely related to an unidentified member of Trichosporon clade, isolated from the xylophagous beetle Phrenapetes bennetti (Tenebrionidae), collected in Panama by Suh et al (2005). Hickey et al (2009) have found T. mycotoxinivorans to be a novel respiratory pathogen in patients with cystic fibrosis. Together, these findings suggest a cosmopolitan habitat and opportunist pathogenicity, which has also been described by Chagas-Neto et al (2008) as common features of this genus.…”
Section: Resultsmentioning
confidence: 99%